Preparation method of nanofiltration membrane, nanofiltration membrane prepared thereby and application of nanofiltration membrane

By regulating the interface polymerization reaction, a nanofiltration membrane with high corrosion resistance was prepared, which solved the problems of unstable structure, low flux and poor high pressure resistance in a high-concentration and strong oxidative acid environment, and achieved efficient acid treatment and separation effects.

CN119548987APending Publication Date: 2025-03-04VONTRON TECH CO LTD

Patent Information

Application Number
CN202311130840.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

When the existing acid-resistant nanofiltration membrane operates in a high-concentration and strong oxidative acid environment, the functional layer structure is unstable, poor tolerant, low flux and not high pressure resistant, which limits its large-scale production and application in the waste acid treatment industry.

Method used

By preparing the cast film liquid, the base film is formed by curing it on the support material, and the base film is contacted with the first phase solution and the second phase solution in turn. The interface polymerization reaction is regulated by using adsorbent, active agent, acid binding agent and crosslinking agent to form a large-area nanofiltration membrane with high density and pressure resistance.

Benefits of technology

The prepared nanofiltration membrane shows excellent tolerance and high throughput in high concentrations of strong oxidative acids such as 25-30% sulfuric acid, 20% hydrochloric acid, 30% nitric acid, and can operate stably for a long time under a high pressure of 4.5MPa. It is suitable for titanium dioxide production, lithium battery raw material extraction and separation, and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119548987A_ABST
    Figure CN119548987A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a nanofiltration membrane, the nanofiltration membrane prepared by the preparation method and application of the nanofiltration membrane. The method comprises the following steps: preparing a membrane casting solution, curing the membrane casting solution on a support material to form a base membrane, and the membrane casting solution comprises a polymer and a solvent; the base membrane is in contact with a first phase solution and a second phase solution in sequence, the first phase solution comprises a first phase monomer, an adsorbent A, an active agent B and an acid-binding agent C, and the second phase solution comprises a second phase monomer and a cross-linking agent D; and post-processing. The nanofiltration membrane disclosed by the invention has excellent tolerance to high-concentration strong oxidizing acid or mixed acid, still keeps high flux and high salt rejection rate even after being soaked in the high-concentration strong oxidizing acid or mixed acid for a long time, can stably operate for a long time under high pressure, and has high flux and high salt rejection rate at the same time; the method can be effectively applied to the fields of waste acid treatment in the titanium dioxide production process, extraction and separation of lithium battery raw materials, mineral product smelting metal ion and acid recovery and the like for filtration and / or separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of separation membranes, and more specifically, to the technical field of nanofiltration membranes resistant to highly corrosive acids. Background Art

[0002] Nanofiltration membranes resistant to highly corrosive acids refer to organic polymer separation membranes that can tolerate and maintain stable structure and performance for a long time in high-concentration strong oxidizing acids or mixed acids such as 25-30% sulfuric acid, 20% hydrochloric acid, and 30% nitric acid. Its main application areas include waste acid treatment in the titanium dioxide production process, extraction and separation of lithium battery raw materials, metal ion and acid recovery in mineral smelting, food, medicine and biological product processing, and removal of organic pollutants in papermaking and dyeing, and other industries with relatively complex and extreme liquid environments. The waste acid concentration is high, the amount to be treated is large, and the acid liquid is highly corrosive (the single component acid concentration is in the range of 25-30%, and the mixed acid concentration is in the range of 10-15%). The production cost of industrial products is high, the treatment process conditions are harsh, and the treatment process technology is insufficient. However, under current actual operating conditions, conventional acid-resistant nanofiltration membranes such as polysulfonamide systems and polyamine systems lack membrane structure tolerance when operating for a long time in a high-concentration, strongly oxidizing acid environment. The membrane system has a short service life (generally about 3 to 6 months), and the membrane element manufacturing cycle is long, and the continuous production efficiency is low, which greatly limits its large-scale promotion and application in the waste acid treatment industry. Therefore, the highly corrosive acid-resistant nanofiltration membrane technology has important theoretical significance and practical application value for guiding the efficient recycling and cost reduction and efficiency improvement of highly oxidizing waste acids in the chemical industry.

[0003] Patent document 1 (US9943811B2) provides a method for preparing an acid-resistant nanofiltration membrane for removing metal ions from mining wastewater. The preparation process is to react a multifunctional amine monomer with a diazine monomer to form a primary ecological membrane, and then immerse it in a sulfuric acid solution of a certain concentration for activation and post-treatment, and finally obtain an acid-resistant nanofiltration membrane with usability. It is then used to treat a copper sulfate solution containing 20% ​​H2SO4. The removal rate of divalent copper ions is about 76%, and the flux is only 2.5gfd. The membrane prepared by this method has good acid resistance, but the removal rate of divalent cations is low, the water output of the membrane assembly is insufficient, and the production cycle is long, which will be unfavorable for the large-scale production and preparation of acid-resistant nanofiltration membranes in industry. Non-patent document 1 (Kah P. Lee, Ju meng Zheng, Nieck E. Benes, et al. pH stable thin film composite polyamine nanofiltration membranes by interfacial polymerization, Journal of Membrane Science, 478 (2015), pages 75-84) uses hyperbranched polyamine as aqueous phase monomer and cyanuric chloride as organic phase monomer to prepare acid-resistant nanofiltration membrane through interfacial cross-linking reaction. The membrane has a MgCl2 removal rate of 96%, a flux of <10 gfd, a low water production, and the end face is usually very easy to deform in a harsh water inlet environment. The pressure resistance is obviously insufficient, and there is still a large gap in meeting the industrial requirements of high flux, high pressure resistance, and oxidation corrosion resistance.

[0004] The production of existing acid-resistant nanofiltration membranes is limited by the preparation materials, and there are very few types to choose from. Its functional layer often requires a high degree of crosslinking and the interfacial polymerization process is uncontrollable. It needs to be activated in the post-treatment process to increase the desalination rate and flux. The basic performance cannot be accurately controlled. The preparation process is intermittent production, the production cycle is long, the production cost is high, the membrane flux is low, only about 10gfd, and the water output of a single 8-inch membrane module is generally <2000GPD. Under complex and harsh operating conditions, if the flux is forcibly increased by increasing the applied pressure (higher than the standard maximum operating pressure of 3.5MPa), the membrane end face is often very easy to deform and then destroy the structural integrity of the membrane assembly, and lose its performance. Especially in the titanium dioxide production industry, the mother liquor sulfuric acid concentration is as high as 25%, which is extremely corrosive, and its tolerance and stability to the functional layer structure of the nanofiltration membrane is a great challenge. This will be unfavorable for the large-scale production, preparation and application of acid-resistant nanofiltration membranes in industry.

[0005] Therefore, improving the high corrosion resistance of conventional acid-resistant nanofiltration membranes and solving the problems of low membrane flux, poor high pressure resistance and low continuous production efficiency are the key technical points that need to be overcome at present. Summary of the invention

[0006] Problem that the invention aims to solve

[0007] The purpose of the present invention is to solve the technical problems of the existing acid-resistant nanofiltration membrane under the operating conditions of high-concentration strong oxidizing acid, such as unstable functional layer structure, poor tolerance, low flux, and high-pressure resistance.

[0008] Solutions for solving problems

[0009] The inventors of the present invention have conducted in-depth research to achieve the above objectives and proposed a method for preparing a nanofiltration membrane as described below, which comprises the following steps:

[0010] Prepare a casting solution, and solidify the casting solution on a supporting material to form a base film, wherein the casting solution comprises a polymer and a solvent;

[0011] The base film is contacted with a first phase solution and a second phase solution in sequence, wherein the first phase solution comprises a first phase monomer, an adsorbent A, an active agent B and an acid binding agent C, and the second phase solution comprises a second phase monomer and a crosslinking agent D;

[0012] After post-treatment, a nanofiltration membrane is obtained.

[0013] In the preparation method of the present invention, the adsorbent A is an acetylacetonate metal salt, and preferably, the acetylacetonate metal salt is at least one of acetylacetonate aluminum, acetylacetonate cobalt, acetylacetonate iron, acetylacetonate manganese, acetylacetonate lithium, acetylacetonate nickel, acetylacetonate copper, acetylacetonate titanium, acetylacetonate palladium, acetylacetonate vanadium, acetylacetonate iridium, acetylacetonate molybdenum, acetylacetonate zirconium, acetylacetonate lanthanum, acetylacetonate ruthenium, acetylacetonate vanadium oxide, acetylacetonate titanium oxide and dihydroxy iridium acetylacetonate.

[0014] The preparation method of the present invention, wherein the active agent B is at least one of sulfates, sulfonates and amine salts containing a linear or branched or cyclic alkyl group having 12 to 18 carbon atoms, preferably, the active agent B is at least one of sodium lauryl sulfate, sodium laurylamide ethyl sulfate, sodium dodecyl sulfate, sodium hexadecyl sulfate, sodium octadecyl sulfate; sodium dioctyl succinate sulfonate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium glycocholate, sodium hexadecylbenzene sulfonate, sodium octadecylbenzene sulfonate, octadecylamine hydrochloride, dioctadecylamine hydrochloride and N,N'-dimethyloctadecylamine hydrochloride.

[0015] In the preparation method of the present invention, the acid-binding agent C is a compound having a five-membered or six-membered nitrogen-containing heterocyclic ring. Preferably, the compound having a five-membered or six-membered nitrogen-containing heterocyclic ring is at least one of an imidazole compound, a pyrimidine compound, a pyridazine compound, a thiazole compound, a pyrazine compound and a pyridine compound.

[0016] In the preparation method of the present invention, the cross-linking agent D is a polyisocyanate compound, preferably, the polyisocyanate compound is at least one of p-phenylene diisocyanate, m-phenylenediisocyanate, toluene-2,4-diisocyanate, toluene-2,5-diisocyanate, 3,3'-dichloro-4,4'-diisocyanate, 1,5-diisocyanate, 4,4'-methylenebis(isocyanate), triphenylmethane triisocyanate and 3,3'-dimethylbiphenyl-4,4'-diisocyanate.

[0017] In the preparation method of the present invention, the first phase monomer is a polyamine compound, preferably, the polyamine compound is a hyperbranched polymer polyamine, and more preferably, the hyperbranched polymer polyamine is at least one of polyetherimide, polyethyleneimine, polyamide-amine, polydopamine, polyethyleneamine, polymethacrylimide and polybismaleimide.

[0018] In the preparation method of the present invention, the second phase monomer is a halogenated five-membered or six-membered nitrogen-containing heterocyclic compound, and preferably, the halogenated five-membered or six-membered nitrogen-containing heterocyclic compound is at least one of a halogenated diazine and a halogenated triazine.

[0019] In the preparation method of the present invention, the polymer is at least one of bisphenol A type PSF, polyaryl sulfone, polyether sulfone, sulfonated polyether sulfone and polyether ether ketone.

[0020] The present invention also provides a nanofiltration membrane prepared according to the preparation method of the present invention.

[0021] The present invention also provides a use of a nanofiltration membrane prepared according to the preparation method of the present invention in filtration and / or separation.

[0022] Effects of the Invention

[0023] The nanofiltration membrane prepared by the method of the present invention has excellent tolerance to high-concentration strong oxidizing acids or mixed acids such as 25-30% sulfuric acid, 20% hydrochloric acid, and 30% nitric acid. Even after long-term immersion in high-concentration strong oxidizing acids or mixed acids, it still maintains high flux and high desalination rate, and can operate stably for a long time under a high pressure of 4.5 MPa while having high flux and high desalination rate. It can be effectively applied to waste acid treatment in the titanium dioxide production process, extraction and separation of lithium battery raw materials, metal ion and acid recovery in mineral smelting, and other fields for filtration and / or separation. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1The results show the relationship between the immersion time of the highly corrosive acid resistant composite nanofiltration membrane 9 prepared in Example 8 in a 25% sulfuric acid solution and the flux and desalination rate of an aqueous solution with a magnesium chloride concentration of 4000 ppm under the operating condition of 110 psi.

[0025] Figure 2 The results show the relationship between the immersion time of the highly corrosive acid resistant composite nanofiltration membrane 9 prepared in Example 8 in a 20% hydrochloric acid solution and the flux and desalination rate of an aqueous solution with a magnesium chloride concentration of 4000 ppm under the operating condition of 110 psi.

[0026] Figure 3 The results show the relationship between the immersion time of the highly corrosive acid resistant composite nanofiltration membrane 9 prepared in Example 8 in a 30% nitric acid solution and the flux and desalination rate of an aqueous solution with a magnesium chloride concentration of 4000 ppm under the operating condition of 110 psi. DETAILED DESCRIPTION

[0027] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.

[0028] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.

[0029] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0030] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0031] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0032] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0033] In this specification, when "normal temperature" or "room temperature" is used, the temperature may be 10-40°C.

[0034] The present invention provides a method for preparing a nanofiltration membrane, which comprises the following steps:

[0035] Prepare a casting solution, and solidify the casting solution on a supporting material to form a base film, wherein the casting solution comprises a polymer and a solvent;

[0036] The base film is contacted with a first phase solution and a second phase solution in sequence, wherein the first phase solution comprises a first phase monomer, an adsorbent A, an active agent B and an acid binding agent C, and the second phase solution comprises a second phase monomer and a crosslinking agent D;

[0037] After post-treatment, a nanofiltration membrane is obtained.

[0038] In the preparation method of the present invention, by introducing adsorbent A into the first phase solution, the first phase monomer can be fully fixed in the micropores of the support layer, promoting a more uniform dispersion of the first phase monomer, thereby playing a role in adjusting the top structural morphology of the functional layer (also called the separation layer), making it more orderly, regular, flat and smooth.

[0039] By introducing the active agent B into the first phase solution, the anchoring ability of the adsorbent A for the first phase monomer can be regulated, thereby controlling the diffusion rate of the first phase monomer, controlling the interfacial polymerization reaction process of the first phase monomer and the second phase monomer, increasing the miscible zone of the interfacial polymerization reaction, and increasing the thickness of the functional layer. This effectively avoids the phenomenon that the thickness of the functional layer of conventional nanofiltration membranes is too thin (usually 40 to 50 nm) due to the uncontrollable interfacial polymerization reaction process (the monomer activity is high, the nascent eco-membrane is formed instantly and is too dense), thereby improving the tolerance of the nanofiltration membrane to highly corrosive acids.

[0040] By introducing the acid binder C into the first phase solution, the interfacial polymerization reaction can be carried out slowly and stably, and the rigid heterocyclic structure of the acid binder C can be embedded in the functional layer to form sub-nano pores, thereby effectively increasing the flux and improving the pressure resistance.

[0041] In addition, by introducing the crosslinker D into the second phase solution, the primary amine and secondary amine remaining after the interfacial polymerization reaction can undergo intermolecular and intramolecular reactions to form a polyurea structure, and then form an interpenetrating network structure with the functional layer, effectively improving the density of the functional layer, thereby increasing the desalination rate (also known as the retention rate) and improving the tolerance of the nanofiltration membrane to highly corrosive acids.

[0042] In the preparation method of the present invention, the adsorbent A is acetylacetone metal salt.

[0043] Preferably, the acetylacetonate metal salt is at least one of acetylacetonate aluminum, acetylacetonate cobalt, acetylacetonate iron, acetylacetonate manganese, acetylacetonate lithium, acetylacetonate nickel, acetylacetonate copper, acetylacetonate titanium, acetylacetonate palladium, acetylacetonate vanadium, acetylacetonate iridium, acetylacetonate molybdenum, acetylacetonate zirconium, acetylacetonate lanthanum, acetylacetonate ruthenium, acetylacetonate vanadium oxide, acetylacetonate titanium oxide and dihydroxy acetylacetonate iridium.

[0044] Preferably, based on the total mass of the first phase solution, the concentration of the adsorbent A is 0.02-0.2%.

[0045] In the preparation method of the present invention, the active agent B is at least one of sulfate, sulfonate and amine salt containing a linear, branched or cyclic alkyl group having 12 to 18 carbon atoms.

[0046] Preferably, the active agent B is at least one of sodium lauryl sulfate, sodium laurylamide ethyl sulfate, sodium dodecyl sulfate, sodium hexadecyl sulfate, sodium octadecyl sulfate; sodium dioctyl succinate sulfonate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium glycocholate, sodium hexadecylbenzene sulfonate, sodium octadecylbenzene sulfonate, octadecylamine hydrochloride, dioctadecylamine hydrochloride and N,N'-dimethyloctadecylamine hydrochloride.

[0047] Preferably, based on the total mass of the first phase solution, the concentration of the active agent B is 0.05-0.5%.

[0048] In the preparation method of the present invention, the acid-binding agent C is a compound having a five-membered or six-membered nitrogen-containing heterocyclic ring.

[0049] Compared with conventional inorganic alkaline acid-binding agents, the acid-binding agent C used in the present invention has a spatial structural advantage, which can make the interfacial polymerization reaction process more moderate, uniform and stable, and it is easier to control the acid-base balance. In addition, the rigid heterocyclic structure of the acid-binding agent C can be embedded in the functional layer to form sub-nanometer channels, thereby effectively improving the flux and the pressure resistance.

[0050] Preferably, the compound having a five-membered or six-membered nitrogen-containing heterocyclic ring is at least one of an imidazole compound, a pyrimidine compound, a pyridazine compound, a thiazole compound, a pyrazine compound and a pyridine compound.

[0051] Preferably, based on the total mass of the first phase solution, the concentration of the acid binding agent C is 0.01-1.0%.

[0052] Preferably, the imidazole compound is at least one of 2-methylimidazole, 1,2-dimethylimidazole, 4-acetylimidazole, imidazole hydrochloride, 1-allyl-3-methylimidazole, 2-mercapto-1-methylimidazole, 2,4-dichloroimidazole, 2-chloro-4-bromoimidazole, 2-bromo-4,5-dichloroimidazole and 2-methyl-4,5-dichloroimidazole and their homologues or derivatives.

[0053] Preferably, the pyrimidine compound is at least one of pyrimethamine, sulfadiazine, 2-aminopyrimidine, 5-aminopyrimidine, sulfadimethoxine, 4,6-dihydroxypyrimidine, 2,4,6-triaminopyrimidine, 2,4-dichloropyrimidine, 2,4,5-trichloropyrimidine, 1,3-dimethylpyrimidine, 4-chloro-6-methylpyrimidine, 2-amino-5-bromopyrimidine and 2-methyl-4-aminopyrimidine and their homologues or derivatives.

[0054] Preferably, the pyridazine compound is at least one of 4-aminopyridazine, sulfachloropyridazine, 3,6-dichloropyridazine, 3-amino-6-chloropyridazine, 3-chloro-6-methylpyridazine, 6-bromopyridazine-3-amine, 6-methyl-3-aminopyridazine, imidazo[1,2-b]pyridazine, 4-hydroxypyridazine, 4-methylpyridazine and 3,6-dichloro-4-methylpyridazine and their homologues or derivatives.

[0055] Preferably, the thiazole compound is at least one of 2,4-dimethylthiazole, 2-propylthiazole, 4,5-dimethylthiazole, 5-thiazolylmethanol, benzothiazole, 6-nitrobenzothiazole, 2,2'-dimethylthiazole, 2,6-dichlorobenzothiazole, 2-amino-4-benzothiazole and 4-methyl-5-acetylthiazole and their homologues or derivatives.

[0056] Preferably, the pyrazine compound is at least one of aminopyrazine, 2-acetylpyrazine, 2-chloropyrazine, 2,3-dimethylpyrazine, 2,5-dimethylpyrazine, 2,3,5-trimethylpyrazine, 2,6-dichloropyrazine, 2-ethyl-5-methylpyrazine, 5-ethyl-2,3-dimethylpyrazine, 2-methylpyrazine and 2-isobutyl-3-methylpyrazine and their homologues or derivatives.

[0057] Preferably, the pyridine compound is at least one of 4-aminopyridine, 4-ethylpyridine, 2-fluoropyridine, 3-aminopyridine, 4-pentylpyridine and pyridine-N-oxide and their homologues or derivatives.

[0058] In the preparation method of the present invention, the cross-linking agent D is a polyisocyanate compound.

[0059] Preferably, the polyisocyanate compound is at least one of p-phenylene diisocyanate, m-phenylenediisocyanate, toluene-2,4-diisocyanate, toluene-2,5-diisocyanate, 3,3'-dichloro-4,4'-diisocyanate, 1,5-diisocyanate, 4,4'-methylenebis(isocyanate), triphenylmethane triisocyanate and 3,3'-dimethylbiphenyl-4,4'-diisocyanate.

[0060] Preferably, based on the total mass of the second phase solution, the concentration of the crosslinking agent D is 0.05-5%.

[0061] The rigid heterocyclic structure of the acid-binding agent C is introduced into the sublayer of the functional layer to form a pressure-resistant transition buffer zone, thereby avoiding irreversible compaction under high pressure; the rigid benzene ring structure of the cross-linking agent D is introduced into the top of the functional layer to form a main pressure-resistant layer; when the nanofiltration membrane operates under high pressure, the two work synergistically to promote the pressure resistance and tolerance to highly corrosive acids of the nanofiltration membrane.

[0062] In the preparation method described in the present invention, the first phase monomer is a polyamine compound, preferably, the polyamine compound is a hyperbranched polymer polyamine, and more preferably, the hyperbranched polymer polyamine is at least one of polyetherimide, polyethyleneimine, polyamide-amine, polydopamine, polyethyleneamine, polymethacrylimide and polybismaleimide.

[0063] Preferably, based on the total mass of the first phase solution, the concentration of the first phase monomer is 1.5% to 6%.

[0064] In the preparation method of the present invention, the second phase monomer is a halogenated five-membered or six-membered nitrogen-containing heterocyclic compound. Preferably, the halogenated five-membered or six-membered nitrogen-containing heterocyclic compound is at least one of a halogenated diazine and a halogenated triazine.

[0065] Preferably, based on the total mass of the second phase solution, the concentration of the second phase monomer is 0.5% to 3%.

[0066] Examples of the halogenated diazines include 3,4-dichloro-5-bromo-1,2-diazine, 3,4-dichloro-6-fluoro-1,2-diazine, 3,4-dichloro-5,6-difluoro-1,2-diazine, 3-chloro-4,5-difluoro-1,2-diazine, 2-chloro-4,5-dibromo-1,3-diazine, 4,5,6-trichloro-1,3-diazine, 2-chloro-4,6-difluoro-1,3-diazine, 2-chloro-4,5,6-tribromo-1,3-diazine, 2,3-dichloro-5,6-dibromo-1,4-diazine, 2,3-dichloro-5,6-difluoro-1,4-diazine, and 2,3-dibromo-5,6-difluoro-1,4-diazine. Examples of the halogenated triazine include trichloro-s-triazine, 2,4-dichloro-6-bromo-s-triazine, 2-chloro-4,6-dibromo-s-triazine, 2-chloro-4-bromo-6-fluoro-s-triazine, 2,4-dibromo-6-fluoro-s-triazine, 4,6-difluoro-s-triazine, 2-chloro-5,6-dibromo-1,3,4-triazine, 2,5-dichloro-6-bromo-1,3,4-triazine, 2-bromo-5,6-difluoro-1,3,4-triazine, 2,5,6-trichloro-1,3,4-triazine, 3-chloro-5,6-dibromo-1,2,4-triazine, 3,5,6-trichloro-1,2,4-triazine, and 3-bromo-5,6-difluoro-1,2,4-triazine.

[0067] Preferably, the present invention uses a hyperbranched polymer polyamine as the first phase monomer and a halogenated five-membered or six-membered nitrogen-containing heterocyclic compound as the second phase monomer, so that the main structure of the cross-linked polymer generated by the interfacial polymerization reaction of the two has a carbon-nitrogen single bond, thereby having sufficient tolerance to highly corrosive acids based on the molecular structure design.

[0068] In the preparation method of the present invention, the polymer is at least one of bisphenol A type PSF, polyaryl sulfone, polyether sulfone, sulfonated polyether sulfone and polyether ether ketone.

[0069] Preferably, the molecular weight of the polymer is in the range of 3000-100000, and the concentration of the polymer is 15-22% based on the total mass of the casting solution.

[0070] Preferably, the solvent used to prepare the casting solution may be at least one of N,N'-dimethylformamide (DMF), N,N'-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP) and dimethyl sulfoxide (DMSO).

[0071] The supporting material is preferably a non-woven fabric, such as PP non-woven fabric.

[0072] The present invention also provides a nanofiltration membrane prepared according to the preparation method of the present invention, which can be advantageously used for filtration and / or separation, and effectively used in the fields of titanium dioxide industry, extraction and separation of lithium battery raw materials, mineral product metallurgy industry, etc.

[0073] Example

[0074] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0075] Comparative Example

[0076] (1) using N,N'-dimethylformamide (DMF) as solvent, preparing a polymer solution with a mass concentration of 16% of bisphenol A polysulfone, setting the coagulation bath temperature at 10-15°C and the line speed at 4 m / min, and scraping on the PP non-woven fabric to form a base film with a thickness of 6.0 mil;

[0077] (2) placing the above-mentioned base film in an aqueous solution containing 0.02% sodium hydroxide and 3.5% polyetherimide (molecular weight 3000Da) at a mass concentration, statically immersing for 60 seconds, taking it out and draining the surface;

[0078] (3) Then, the mixture was placed in a hexane solution containing 1% trichlorotriazine by mass concentration and taken out after being immersed for 60 seconds;

[0079] (4) Then, the membrane was washed with pure water for three times, immersed in a glycerol solution for 30 min for pore preservation, and then placed in a vacuum oven at 85° C. for 10 min for heat treatment, thereby obtaining a composite nanofiltration membrane 1.

[0080] Composite nanofiltration membrane 1 was operated at 110 psi in an aqueous solution with a magnesium chloride concentration of 4000 ppm for 30 min, with a retention rate of 96.32% and a flux of 20.4 L / m 2 h.

[0081] Example 1

[0082] (1) Using N,N'-dimethylformamide (DMF) as solvent, a polymer solution with a mass concentration of 16% of bisphenol A polysulfone was prepared, the coagulation bath temperature was 10-15°C, the line speed was 4m / min, and a base film with a thickness of 6.0 mil was scraped on the PP non-woven fabric by a scraper;

[0083] (2) placing the above-mentioned base film in an aqueous solution containing 0.02% aluminum acetylacetonate, 0.05% sodium laurylamide ethyl sulfate, 0.01% 4-acetylimidazole and 3.5% polyetherimide (molecular weight 3000Da), statically immersing for 60 seconds, taking out and draining the surface;

[0084] (3) Then, the mixture was placed in a hexane solution containing 0.05% by mass of p-phenylene diisocyanate and 1% by mass of trichlorotriazine, and taken out after being immersed for 60 seconds;

[0085] (4) Then, the membrane was washed with pure water for three times, immersed in a glycerol solution for 30 min for pore preservation, and then placed in a vacuum oven at 85° C. for heat treatment for 10 min, to finally obtain a composite nanofiltration membrane 2 resistant to highly corrosive acids.

[0086] The composite nanofiltration membrane 2 resistant to highly corrosive acid was operated in an aqueous solution with a magnesium chloride concentration of 4000 ppm under 110 psi operating conditions for 30 min, with a retention rate of 99.16% and a flux of 41.3 L / m 2 h.

[0087] Example 2

[0088] (1) using N,N'-dimethylformamide (DMF) as solvent, preparing a polymer solution with a mass concentration of 17% of bisphenol A polysulfone, setting the coagulation bath temperature at 10-15°C and the line speed at 4 m / min, and scraping a base film with a thickness of 6.0 mil on a PP non-woven fabric by a scraper;

[0089] (2) placing the above-mentioned base film in an aqueous solution containing 0.04% ferric acetylacetonate, 0.1% sodium lauryl sulfate, 0.03% 1,2-dimethylimidazole and 3.5% polyetherimide (molecular weight 6000Da), statically immersing for 120 seconds, taking out and draining the surface;

[0090] (3) Then, the mixture was placed in a hexane solution containing 0.1% by mass of m-xylylenediisocyanate and 1% by mass of trichlorotriazine, and taken out after being immersed for 120 seconds;

[0091] (4) Then, the membrane was washed with pure water for three times, immersed in a glycerol solution for 30 min for pore preservation, and then placed in a vacuum oven at 85° C. for heat treatment for 10 min, to finally obtain a composite nanofiltration membrane 3 resistant to highly corrosive acids.

[0092] The composite nanofiltration membrane 3 resistant to highly corrosive acid was operated at 110 psi in an aqueous solution with a magnesium chloride concentration of 4000 ppm for 30 min, with a retention rate of 99.10% and a flux of 46.1 L / m 2h.

[0093] Example 3

[0094] (1) using N,N'-dimethylformamide (DMF) as solvent, preparing a polymer solution with a mass concentration of 18% of bisphenol A polysulfone, setting the coagulation bath temperature at 10-15°C and the line speed at 4 m / min, and scraping a base film with a thickness of 6.0 mil on a PP non-woven fabric by a scraper;

[0095] (2) placing the above-mentioned base film in an aqueous solution containing 0.08% manganese acetylacetonate, 0.15% sodium hexadecyl sulfate, 0.05% 4-aminopyridine and 3.5% polyetherimide (molecular weight 8000Da), statically immersing for 240 seconds, taking out and draining the surface;

[0096] (3) Then, the mixture was placed in a hexane solution containing 0.5% by mass of toluene-2,4-diisocyanate and 1% by mass of trichloro-s-triazine, and taken out after being immersed for 240 seconds;

[0097] (4) Then, the membrane was washed with pure water for three times, immersed in a glycerol solution for 30 min for pore preservation, and then placed in a 90° C. vacuum oven for heat treatment for 10 min, to finally obtain a composite nanofiltration membrane 4 resistant to highly corrosive acids.

[0098] The composite nanofiltration membrane 4 resistant to highly corrosive acid was operated at 110 psi in an aqueous solution with a magnesium chloride concentration of 4000 ppm for 30 min, with a retention rate of 99.03% and a flux of 50.3 L / m 2 h.

[0099] Example 4

[0100] (1) Using N,N'-dimethylacetamide (DMAc) as a solvent, a polymer solution with a mass concentration of 18% of bisphenol A polysulfone was prepared, the coagulation bath temperature was 10-15°C, the line speed was 4 m / min, and a base film with a thickness of 6.0 mil was scraped on the PP non-woven fabric by a scraper;

[0101] (2) placing the above-mentioned base film in an aqueous solution containing 0.1% ruthenium acetylacetonate, 0.2% sodium octadecylbenzene sulfonate, 0.1% sulfadimethoxine and 3.5% polyetherimide (molecular weight 10000Da), statically immersing for 240 seconds, taking out and draining the surface;

[0102] (3) then, placing it in a n-hexane solution containing 1% by mass concentration of toluene-2,5-diisocyanate and 1% by mass concentration of trichloro-s-triazine, and taking it out after immersing it for 240 seconds;

[0103] (4) Then, the membrane was washed with pure water for three times, immersed in a glycerol solution for 30 min for pore preservation, and then placed in a vacuum oven at 85° C. for 10 min for heat treatment, thereby obtaining a composite nanofiltration membrane 5 resistant to highly corrosive acids.

[0104] The composite nanofiltration membrane 5 resistant to highly corrosive acid was operated at 110 psi in an aqueous solution with a magnesium chloride concentration of 4000 ppm for 30 min, with a retention rate of 98.86% and a flux of 58.7 L / m 2 h.

[0105] Example 5

[0106] (1) Using N,N'-dimethylacetamide (DMAc) as a solvent, a polymer solution with a mass concentration of 19% of bisphenol A polysulfone was prepared, the coagulation bath temperature was 10-15°C, the line speed was 4m / min, and a base film with a thickness of 6.0 mil was scraped on the PP non-woven fabric by a scraper;

[0107] (2) placing the above-mentioned base film in an aqueous solution containing 0.12% lanthanum acetylacetonate, 0.25% sodium dioctyl sulfosuccinate, 0.2% 6-methyl-3-aminopyridazine and 3.5% polyetherimide (molecular weight 20000Da), statically immersing for 360 seconds, taking out and draining the surface;

[0108] (3) Then, the mixture was placed in a hexane solution containing 1.0% 3,3'-dichloro-4,4'-diisocyanate and 1% trichloro-s-triazine, and taken out after being immersed for 360 seconds;

[0109] (4) Then, the membrane was washed with pure water for three times, immersed in a glycerol solution for 30 min for pore preservation, and then placed in a 90°C vacuum oven for heat treatment for 10 min, to finally obtain a composite nanofiltration membrane 6 resistant to highly corrosive acids.

[0110] The composite nanofiltration membrane 6 resistant to highly corrosive acid was operated at 110 psi in an aqueous solution with a magnesium chloride concentration of 4000 ppm for 30 min, with a retention rate of 98.72% and a flux of 65.6 L / m 2 h.

[0111] Example 6

[0112] (1) Using N-methylpyrrolidone (NMP) as a solvent, a polymer solution with a mass concentration of 19% of bisphenol A polysulfone was prepared, the coagulation bath temperature was 10-15° C., the line speed was 4 m / min, and a base film with a thickness of 6.0 mil was scraped on the PP non-woven fabric by a scraper;

[0113] (2) placing the above-mentioned base film in an aqueous solution containing 0.14% lithium acetylacetonate, 0.3% sodium glycocholate, 0.2% 2-ethyl-5-methylpyrazine, and 3.5% polyetherimide (molecular weight 40,000 Da), statically immersing for 360 seconds, taking out and draining the surface;

[0114] (3) Subsequently, the mixture was placed in a hexane solution containing 2.0% by mass of 4,4'-methylenebis(isocyanate) and 1% by mass of trichloro-s-triazine, and taken out after being immersed for 360 seconds;

[0115] (4) Then, the membrane was washed with pure water for three times, immersed in a glycerol solution for 30 min for pore preservation, and then placed in a vacuum oven at 85°C for 10 min for heat treatment, to finally obtain a composite nanofiltration membrane 7 resistant to highly corrosive acids.

[0116] The composite nanofiltration membrane 7 resistant to highly corrosive acid was operated at 110 psi in an aqueous solution with a magnesium chloride concentration of 4000 ppm for 30 min, with a retention rate of 99.24% and a flux of 58.1 L / m 2 h.

[0117] Example 7

[0118] (1) Using N-methylpyrrolidone (NMP) as a solvent, a polymer solution with a mass concentration of 20% of bisphenol A polysulfone was prepared, the coagulation bath temperature was 10-15° C., the line speed was 4 m / min, and a base film with a thickness of 6.0 mil was scraped on the PP non-woven fabric by a scraper;

[0119] (2) placing the above-mentioned base film in an aqueous solution containing 0.16% vanadium acetylacetonate, 0.4% dioctadecylamine hydrochloride, 0.2% 2,3,5-trimethylpyrazine and 3.5% polyetherimide (molecular weight 80000Da), statically immersing for 420 seconds, taking out and draining the surface;

[0120] (3) Then, the mixture was placed in a hexane solution containing 3% by mass of 3,3'-dimethylbiphenyl-4,4'-diisocyanate and 1% by mass of trichloro-s-triazine, and taken out after being immersed for 420 seconds;

[0121] (4) Then, the membrane was washed with pure water for three times, immersed in a glycerol solution for 30 min for pore preservation, and then placed in a 90° C. vacuum oven for heat treatment for 10 min, to finally obtain a composite nanofiltration membrane 8 resistant to highly corrosive acids.

[0122] The composite nanofiltration membrane 8 resistant to highly corrosive acid was operated at 110 psi in an aqueous solution with a magnesium chloride concentration of 4000 ppm for 30 min, with a retention rate of 99.40% and a flux of 55.8 L / m 2 h.

[0123] Example 8

[0124] (1) Using N-methylpyrrolidone (NMP) as a solvent, a polymer solution with a mass concentration of 21% of bisphenol A polysulfone was prepared, the coagulation bath temperature was 10-15° C., the line speed was 4 m / min, and a base film with a thickness of 6.0 mil was scraped on the PP non-woven fabric by a scraper;

[0125] (2) placing the above-mentioned base film in an aqueous solution containing 0.2% nickel acetylacetonate, 0.5% N,N'-dimethyloctadecylamine hydrochloride, 0.2% 4-methyl-5-acetylthiazole and 3.5% polyetherimide (molecular weight 100000Da), statically immersing for 540 seconds, taking out and draining the surface;

[0126] (3) Then, the mixture was placed in a hexane solution containing 4.0% triphenylmethane triisocyanate and 1% trichlorotriazine, and taken out after being immersed for 540 seconds;

[0127] (4) Then, the membrane was washed with pure water for three times, immersed in a glycerol solution for 30 min for pore preservation, and then placed in a 90° C. vacuum oven for heat treatment for 10 min, to finally obtain a composite nanofiltration membrane 9 resistant to highly corrosive acids.

[0128] The composite nanofiltration membrane 9 resistant to highly corrosive acid was operated at 110 psi in an aqueous solution with a magnesium chloride concentration of 4000 ppm for 30 min, with a retention rate of 99.54% and a flux of 51.5 L / m 2 h.

[0129] The highly corrosive acid resistant composite nanofiltration membranes 2 to 9 prepared in Examples 1 to 8 were immersed in 25% sulfuric acid solution, 20% hydrochloric acid solution, and 30% nitric acid solution for 1440 hours, respectively. They were then taken out and washed with pure water. The morphology of each highly corrosive acid resistant composite nanofiltration membrane was observed, and the results showed that no deformation occurred and the structural integrity was maintained.

[0130] Figures 1 to 3The results of the flux and desalination rate of the highly corrosive acid resistant composite nanofiltration membrane 9 prepared in Example 8 after being soaked in 25% sulfuric acid solution, 20% hydrochloric acid solution, and 30% nitric acid solution for different time periods, taken out and washed with pure water, and then run for 30 minutes for an aqueous solution with a magnesium chloride concentration of 4000 ppm at an operating pressure of 110 psi are shown. The results show that the flux is maintained at 50 L / m 2 h, the desalination rate was kept above 99%. After soaking in each acid solution for 1440 hours, the desalination rates reached 99.45%, 99.20% and 99.04% respectively.

[0131] Table 1 below shows the results of flux and desalination rate of an aqueous solution with a magnesium chloride concentration of 4000 ppm when the highly corrosive acid resistant composite nanofiltration membrane 9 prepared in Example 8 was operated at a pressure of 4.5 MPa for different time periods.

[0132] Table 1

[0133]

[0134] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.

[0135] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A method for preparing a nanofiltration membrane, characterized in that: It includes the following steps: Prepare a casting solution, and solidify the casting solution on a supporting material to form a base film, wherein the casting solution comprises a polymer and a solvent; The base film is contacted with a first phase solution and a second phase solution in sequence, wherein the first phase solution comprises a first phase monomer, an adsorbent A, an active agent B and an acid binding agent C, and the second phase solution comprises a second phase monomer and a crosslinking agent D; After post-treatment, a nanofiltration membrane is obtained.

2. The preparation method according to claim 1, wherein the adsorbent A is an acetylacetonate metal salt, preferably, the acetylacetonate metal salt is at least one of acetylacetonate aluminum, acetylacetonate cobalt, acetylacetonate iron, acetylacetonate manganese, acetylacetonate lithium, acetylacetonate nickel, acetylacetonate copper, acetylacetonate titanium, acetylacetonate palladium, acetylacetonate vanadium, acetylacetonate iridium, acetylacetonate molybdenum, acetylacetonate zirconium, acetylacetonate lanthanum, acetylacetonate ruthenium, acetylacetonate vanadium oxide, acetylacetonate titanium oxide and dihydroxy iridium acetylacetonate.

3. The preparation method according to claim 1 or 2, wherein the active agent B is at least one of a sulfate, sulfonate and amine salt containing a linear or branched or cyclic alkyl group having 12 to 18 carbon atoms, preferably, the active agent B is at least one of sodium lauryl sulfate, sodium laurylamide ethyl sulfate, sodium dodecyl sulfate, sodium hexadecyl sulfate, sodium octadecyl sulfate; sodium dioctyl succinate sulfonate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium glycocholate, sodium hexadecylbenzene sulfonate, sodium octadecylbenzene sulfonate, octadecylamine hydrochloride, dioctadecylamine hydrochloride and N,N'-dimethyloctadecylamine hydrochloride.

4. The preparation method according to claim 1 or 2, wherein the acid binding agent C is a compound having a five-membered or six-membered nitrogen-containing heterocyclic ring, preferably, the compound having a five-membered or six-membered nitrogen-containing heterocyclic ring is at least one of an imidazole compound, a pyrimidine compound, a pyridazine compound, a thiazole compound, a pyrazine compound and a pyridine compound.

5. The preparation method according to claim 1 or 2, wherein the crosslinking agent D is a polyisocyanate compound, preferably, the polyisocyanate compound is at least one of p-phenylene diisocyanate, m-phenylenediisocyanate, toluene-2,4-diisocyanate, toluene-2,5-diisocyanate, 3,3'-dichloro-4,4'-diisocyanate, 1,5-diisocyanate, 4,4'-methylenebis(isocyanate), triphenylmethane triisocyanate and 3,3'-dimethylbiphenyl-4,4'-diisocyanate.

6. The preparation method according to claim 1 or 2, wherein the first phase monomer is a polyamine compound, preferably, the polyamine compound is a hyperbranched polymer polyamine, more preferably, the hyperbranched polymer polyamine is at least one of polyetherimide, polyethyleneimine, polyamide-amine, polydopamine, polyethyleneamine, polymethacrylimide and polybismaleimide.

7. The preparation method according to claim 1 or 2, wherein the second phase monomer is a halogenated five-membered or six-membered nitrogen-containing heterocyclic compound, preferably, the halogenated five-membered or six-membered nitrogen-containing heterocyclic compound is at least one of a halogenated diazine and a halogenated triazine.

8. The preparation method according to claim 1 or 2, wherein the polymer is at least one of bisphenol A type PSF, polyaryl sulfone, polyether sulfone, sulfonated polyether sulfone and polyether ether ketone.

9. A nanofiltration membrane obtained according to the preparation method according to any one of claims 1 to 8.

10. Use of the nanofiltration membrane according to claim 9 in filtration and / or separation.

Citation Information

Patent Citations

  • Solvent and acid stable membranes, methods of manufacture thereof and methods of use thereof inter alia for separating metal ions from liquid process streams

    US9943811B2

Cited By

  • Acid-resistant nanofiltration membrane and preparation method thereof

    CN121972018A

  • Acid-resistant nanofiltration membrane and preparation method thereof

    CN121972018B

  • Bionic strong acid-resistant nanofiltration membrane and preparation method thereof

    CN122006501A

  • Alkali-resistant film for paper pulp waste liquid treatment and preparation method of alkali-resistant film

    CN122252047A